2018
DOI: 10.1002/cjce.23180
|View full text |Cite
|
Sign up to set email alerts
|

Detailed CFD modelling of fast pyrolysis of different biomass types in fluidized bed reactors

Abstract: In the present study, an Eulerian-Eulerian computational fluid dynamics (CFD) model, combined with a comprehensive biomass reaction scheme, was used to simulate fast pyrolysis of four different biomass types in the fluidized bed reactors. The study focuses on the influence of biomass components of different biomass types on the yields, formations, and contents of compositions of pyrolysis products. The result showed that the bio-oil yield of cellulose-rich biomass was higher than other biomass types, and char … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For instance, ANSYS FLUENT [25,44,47,[52][53][54], Multiphase Flow with Interphase eXchanges (MFIX) [33,37,55,56], OpenFOAM [26,27,29,30,35,38,57,58] etc. have been used frequently for simulation of reacting multiphase flow including combustion [52], gasification [52][53][54] and pyrolysis process [44,47,48,52,56,59]. Among them, ANSYS FLUENT has attracted the attention of engineers and researchers due to features including its user-friendly environment, capability of modelling complex geometries inside ANSYS workbench interface, programming facility by adding user defined functions (UDF), having most recent empirical correlations for granular heat transfer and drag as well as the KTFG (Kinetic Theory of Granular Flow); models that are needed for description of interphase transport phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ANSYS FLUENT [25,44,47,[52][53][54], Multiphase Flow with Interphase eXchanges (MFIX) [33,37,55,56], OpenFOAM [26,27,29,30,35,38,57,58] etc. have been used frequently for simulation of reacting multiphase flow including combustion [52], gasification [52][53][54] and pyrolysis process [44,47,48,52,56,59]. Among them, ANSYS FLUENT has attracted the attention of engineers and researchers due to features including its user-friendly environment, capability of modelling complex geometries inside ANSYS workbench interface, programming facility by adding user defined functions (UDF), having most recent empirical correlations for granular heat transfer and drag as well as the KTFG (Kinetic Theory of Granular Flow); models that are needed for description of interphase transport phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The important factors, including biomass types, heating rate, and temperature, in the pyrolysis process have been studied by some researchers [20][21][22][23]. The fast pyrolysis of four different biomass types was examined by Eri et al via detailed CFD modelling [23].…”
Section: Introductionmentioning
confidence: 99%
“…The important factors, including biomass types, heating rate, and temperature, in the pyrolysis process have been studied by some researchers [20][21][22][23]. The fast pyrolysis of four different biomass types was examined by Eri et al via detailed CFD modelling [23]. Their study showed that cellulose-rich biomass produced the highest bio-oil yield, and the generated char was mainly from the lignin and cellulose of the biomass.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the Computational Fluid Dynamic (CFD) method has been recognized as a useful tool in predicting the product yields of chemical processes, as well as plant design and optimization. Most of the recent CFD studies were applied to biomass pyrolysis in fluidized bed reactors [19][20][21][22][23]. Papadikis et al [24][25][26][27][28][29] simulated biomass fast pyrolysis in fluidized beds assuming two Eulerian phases and one Lagrangian phase in a 3-D domain.…”
Section: Introductionmentioning
confidence: 99%